Studies on Miscibility of a Copolyester of Bisphenol-A with Terephthalic and Isophthalic Acids and Poly(methyl methacrylate) Blends in Dilute Solution - Isik, B.; Cakar, F.; Cankurtaran, O. (PLEIADES PUBLISHING LTD, 2021)
The miscibility behavior of the blends of a copolyester of bisphenol-A with terephthalic and isophthalic acids in equal ratio and poly(methyl methacrylate) was studied by different experimental techniques. The intrinsic viscosities were determined for several copolyesters of bisphenol-A with terephthalic and isophthalic acids in equal ratio and poly(methyl methacrylate) blends in dilute chloroform solutions at 25 degrees C by viscometric analysis. From experimental results of the intrinsic viscosities of the polymer blends, some miscibility parameters were obtained by applying the criteria proposed by some research groups. The miscibility of the blends was also studied using Fourier transform infrared spectroscopy and differential scanning calorimeter.
Keywords: POLYMER; COMPATIBILITY; MORPHOLOGY; MIXTURES; WATER; Polymer Science